(untitled) (KULT_online, 2013)
In her study Maschinen zuhause. Die Technisierung des Wohnens in der Moderne (Machines at Home: Mechanisation of Living in Modernity), Katrin Eberhard explores the transformations of home technologies during the 1920s and 30s from the perspectives of architectural theory and cultural studies. On the basis of selected buildings she describes how technical infrastructures and media changed the dwellings of the social, and examines the architectural consequences they prompted.